1994
DOI: 10.1021/ef00046a015
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Coal Liquefaction. 3. Catalytic Reactions of Polyfunctional Compounds

Abstract: Substituent effects relevant to coal chemistry were studied using polyfunctional aromatic compounds in catalytic reactions under coal liquefaction conditions. The compounds utilized were nhexyldibenzothiophene (I), 6-methyl-9-(l-methylethyl)dibenzothiophen-4-ol (II), and 4-methoxy-6-methyl-9-(l-methylethyl)dibenzothiophene (III). Reactions were performed in the presence of an H donor at temperatures of 350-430 °C; catalysts utilized in this study consist of carbon black, iron oxides (magnetite and ferrihydrite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…When hydrogen partial pressure was increased to 6.0 MPa (Figure 2b), the difference in anthracene conversion and hydrogenated product distribution between the activated carbon and glass beads, particularly at higher temperatures, becomes greater, further confirming the catalytic activity of the activated carbon in the hydrogenation of anthracene. In addition, a small amount of a 6-butyltetralin (BuTet) as well as phenanthrene (Phen) was also observed over the activated carbon under 6.0 MPa of H 2 at 400 °C, might suggesting a slightly catalytic activity of the activated carbon in the cleavage of C-C bonds [4][5][6][7] and ring isomerization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When hydrogen partial pressure was increased to 6.0 MPa (Figure 2b), the difference in anthracene conversion and hydrogenated product distribution between the activated carbon and glass beads, particularly at higher temperatures, becomes greater, further confirming the catalytic activity of the activated carbon in the hydrogenation of anthracene. In addition, a small amount of a 6-butyltetralin (BuTet) as well as phenanthrene (Phen) was also observed over the activated carbon under 6.0 MPa of H 2 at 400 °C, might suggesting a slightly catalytic activity of the activated carbon in the cleavage of C-C bonds [4][5][6][7] and ring isomerization.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally known that some of them catalyze reactions such as chlorinations, oxidations of SO 2 , NO, and H 2 S, and oxidative dehydrogenations of hydrocarbons as well as alcohols. Additionally, some recent studies have shown that some carbon materials are active for the cleavage of C−C bonds, degradation of polyethylene, , dehydrogenation of hydrocarbons, , and dehydration as well as dehydrogenation of ethanol, 2-propanol, and 2-butanol. Under reduction conditions in the presence of hydrogen donor solvents, they are also found to catalyze the hydrogenolysis of benzyl-methylnaphthalenes and the dehydroxylation and dehalogenation of substituted polycyclic aromatics with the hydrogenation of ring . All these suggest that carbon materials used as supports may not be innocent, but may function as catalysts in some reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The catalytic activity of activated carbon during the reaction of DNE in DHP under a hydrogen atmosphere was first examined, because Farcasiu et al reported that carbon materials such as carbon blacks had catalytic activities for hydrocracking and the other reactions relevant to coal liquefaction. The conversion and the decomposition in the absence of the activated carbon were 21.1 and 19.0% (run 1), and then the conversion and the decomposition increased to 44.8 and 33.5%, respectively, when the activated carbon was added (run 5). This fact clearly shows that the activated carbon catalyzes the cracking of DNE.…”
Section: Resultsmentioning
confidence: 99%
“…1989;andMalhotra, 1990, 1992) Recently, polyfunctional model compounds which contain several functionalities found in coal have also been examined (Farcasiu et al. , 1994b.…”
Section: Model Compoundsmentioning
confidence: 99%